Stator current identification in generator among single and composite faults composed by static air‐gap eccentricity and rotor inter‐turn short circuit. Issue 2 (12th November 2022) - He, Yu‐Ling; Qiu, Ming‐Hao; Jiang, Meng‐Ya; Zhou, Fu‐Cheng; Gerada, David; Zhang, Xiao‐Chen; Du, Xiao‐Dong
Abstract: In this study, a fault diagnosis model based on magnetic density is proposed to analyse the current characteristics of synchronous generator rotor inter‐turn short circuit and air gap eccentric single fault and composite fault. The model considers the influence of rotor inter‐turn short circuit and air gap eccentricity on air gap magnetic density. According to two main factors, the short circuit turns and eccentric distance, are used to reflect the short circuit and eccentricity of the generator. The detailed parameter input model of the generator can easily and quickly predict the development trend of these current parameters based on the air gap magnetic density. And the phase current is selected as the current parameter. The validity of the proposed model is verified by two‐dimensional finite element analysis and experimental research. Abstract : In this paper, a fault diagnosis model based on magnetic density is proposed to analyze the electromechanical characteristics of synchronous generator rotor turn‐to‐turn short circuit and air gap eccentric single fault and composite fault.